The Effect Of Probiotics On Dairy Products - А.Xatamov; J.B. Qozoqov (Zien Journals, 2022)
This article describes the importance of probiotic feeding of chowder, the effect of chowder on milk productivity and growth indicators of lambs.
Keywords: milk productivity; probiotic feeding of chowder